Technical and Economic Analysis of Photovoltaic System Designed for a Public Building in Turkey - (:unkn) unknown (INT JOURNAL RENEWABLE ENERGY RESEARCH, 2019)
The use of renewable energy sources is a clean and sustainable solution in order to meet increasing energy needs. Photovoltaic systems can produce electricity directly from solar energy which the fastest growing types of renewable energy in Turkey. The use of photovoltaic systems in public buildings will contribute to awareness of renewable energy as well as supporting the electricity consumption of these buildings. In this study, a photovoltaic system has been designed for a public building in Istanbul to compare electricity consumption with a traditional system. The system was designed and simulated with PV*SOL software. As a result of the comparison, environmental and economic analysis have been made. Roof of the four blocks and the open car park located on south side of the building were set for installation of the system. The cost of the system having installed capacity of 3.259 MW is supposed to be USD 2,705,586. Payback time would be 5.3 years. Performance coefficient of the system is expected to be 86.3%. Annual 4.10 GWh electrical energy for the building can be produced by photovoltaic system. Economic and environmental evaluations have been carried out for the designed photovoltaic system.
Keywords: Photovoltaic system; public building; rooftop; car park; Istanbul